Analisis SWOT Palang Merah Indonesia (PMI) dalam Melakukan Pengurangan Risiko Bencana di Kota Padang - Andre Lofika Pegi (Faculty of Social Science, Universitas Negeri Padang, 2019)
The purpose of this study was to find out and analyze the strengths, weaknesses, opportunities and threats encountered by the Indonesian Red Cross (PMI) in carrying out disaster risk reduction in the Padang City. The method used in the study is descriptive qualitative method with data collection techniques through interviews and documentation studies. Data were analyzed using SWOT analysis. This research shows that the strengths are, PMI has reliable personnel and specialists in their fields, PMI has a stable procedure and system, PMI has its own law, namely Law No. 1 of 2018 and Government Regulation No. 7 of 2019. The disadvantage is that PMI is a voluntary organization so that in carrying out its duties PMI cannot be too forced and not too binding, PMI does not have a budget for risk reduction so it is difficult to carry out operational activities, infrastructure and equipment in PMI are incomplete, PMI personnel quantity still less especially the stanbey at headquarters. The opportunity that PMI has in carrying out disaster risk reduction, namely PMI, has gained trust from the government, the PMI name is quite good in the government and society. The threat is that community participation is still lacking when conducting socialization activities on disaster risk reduction, PMI is used as political land by certain elements of the external PMI, causing internal conflicts and influencing PMI's performance. The efforts made by PMI in conducting disaster risk reduction in the Padang City by conducting a new volunteer open recruitment if the volunteers have begun to be less active, provide training in advance to the team that will take to the field to provide socialization so that it is more prepared and the information delivered is more dense and quality, maintaining communication with the same stakeholders engaged in disaster management, conducting regular and periodic meetings to maintain communication and facilitating coordination among fellow stakeholders, calling on the public to always participate in socialization activities or simulations held by PMI and other stakeholders. Keywords: SWOT analysis, PMI, Disaster Risk Management